Half of geriatric trauma patients have significant ocular disease: Findings of a novel trauma provider eye examination for vision screening. Issue 1 (July 2021) - Bardes, James M.; Grabo, Daniel J.; Donovan, James; Albuquerque, Alexander; Coleman, Kennith Conley; Wen, Sijin; Wilson, Alison; Nguyen, John; Bardes, Allison
Abstract : BACKGROUND: Geriatric ground level fall is a common admission diagnosis for trauma centers in the United States. Visual health has been linked to fall risk reduction in older adult but is rarely fully evaluated during a trauma admission. Using a commercial application and a questionnaire, we developed and tested a trauma provider eye examination (TPEE) to screen visual health. This study used the TPEE to (1) evaluate the prevalence of undiagnosed or undertreated visual disease in geriatric trauma patients and (2) determine the feasibility and reliability of the TPEE to screen for vision disease. METHODS: This prospective study included patients older than 60 years evaluated by the trauma service from June 2019 to May 2020. Patients with ocular or globe trauma were excluded. The primary outcome was significant abnormal vision (SAV) found using the TPEE. Ophthalmology performed a dilated examination as the criterion standard for comparison. We assessed the feasibility and reliability of the TPEE. Fisher's exact test and logistic model were used in the data analysis. RESULTS: Enrollment concluded with 96 patients. Mean age was 75 years, and fall (79%) was the most common mechanism of injury. Significant abnormal vision was common: undiagnosed disease was found in 39% and undertreated in 14%. Trauma provider examination was 94% sensitive and 92% specific for SAV cases. Congruence between TPEE and ophthalmology examination was highest in pupil examination (86%), visual fields (58%), and Amsler grid (52%). Multivariate analysis found that a combination of an abnormal Amsler test and abnormal visual field defect was significantly associated with SAV (odds ratio, 4.1; p = 0.03). CONCLUSION: Trauma provider eye examination screening can identify patients with visual deficits. Given the association between visual deficits and fall risk, older adults may benefit from such a screening or a formal ophthalmology referral. LEVEL OF EVIDENCE: Therapeutic/Care Management, level II. Abstract : Supplemental digital content is available in the text.